Elevated antibody to D-alanyl lipoteichoic acid indicates caries experience associated with fluoride and gingival health - Owen Willis L; Avery Kevin T; Brumley Robert L; Levine Martin; Parker Donald E (BMC, 2002)
Background Acidogenic, acid-tolerant bacteria induce dental caries and require D-alanyl glycerol lipoteichoic acid (D-alanyl LTA) on their cell surface. Because fluoride inhibits acid-mediated enamel demineralization, an elevated antibody response to D-alanyl LTA may indicate subjects with more acidogenic bacteria and, therefore, an association of DMFT with fluoride exposure and gingival health not apparent in low responders. Methods Cluster analysis was used to identify low antibody content. Within low and high responders (control and test subjects), the number of teeth that were decayed missing and filled (DMFT), or decayed only (DT) were regressed against fluoride exposure in the water supply and from dentrifice use. The latter was determined from gingival health: prevalences of plaque (PL) and bleeding on probing (BOP), and mean pocket depth (PD). Age was measured as a possible confounding cofactor. Results In 35 high responders, DMFT associated with length of exposure to fluoridated water (F score), PL and BOP (R2 = 0.51, p < 0.001), whereas in 67 low D-ala-IgG responders, DMFT associated with PL, age, and PD (R2 = 0.26, p < 0.001). BOP correlated strongly with number of 7 7 decayed teeth (DT) in 54 high responders (R2 = 0.57, p < 0.001), but poorly in 97 low responders (R2 = 0.12, p < 0.001). The strength of the PD association with DMFT, or of BOP with DT, in high responders significantly differed from that in low responders (p < 0.05). Conclusion Caries associates with gingival health and fluoridated water exposure in high D-alanyl LTA antibody responders.